The (ir)relevance of science fiction to non-binary and genderqueer readers - Šporčič, Anamarija (ELOPE (Ljubljana), 2018)
As an example of jean Baudrillard's third order of simulacra, contemporary science fiction represents a convenient literary platform for the exploration of our current and future understanding of gender, gender variants and gender fluidity. The genre should, in theory, have the advantage of being able to avoid the limitations posed by cultural conventions and transcend them in new and original ways. In practice, however, literary works of science fiction that are not subject to the dictations of the binary understanding of gender are few and far between, as authors overwhelmingly use the binary gender division as a binding element between the fictional world and that of the reader. The reversal of gender roles, merging of gender traits, androgynous characters and genderless societies nevertheless began to appear in the 1960s and 1970s. This paper briefly examines the history of attempts at transcending the gender binary in science fiction, and explores the possibility of such writing empowering non-binary/genderqueer individuals.
Keywords: fluidnost spola; gender fluidity; gender narrative; gender studies; gender variants; genderqueer; nebinarne spolne identitete; non-binary gender identities; odziv bralstva; ospoljena pripoved; raznolikost spolov; reader response; science fiction; študije spola; znanstvena fantastika